2022
DOI: 10.1126/science.abl6773
|View full text |Cite
|
Sign up to set email alerts
|

Microglia-mediated degradation of perineuronal nets promotes pain

Abstract: Activation of microglia in the spinal cord dorsal horn following peripheral nerve injury contributes to the development of pain hypersensitivity. How activated microglia selectively enhance the activity of spinal nociceptive circuits is not well understood. We discovered that following peripheral nerve injury, microglia degrade extracellular matrix structures, perineuronal nets (PNNs), in lamina I of the spinal cord dorsal horn. Lamina I PNNs selectively enwrap spinoparabrachial projection neurons, which integ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(59 citation statements)
references
References 44 publications
0
44
0
Order By: Relevance
“…Activated microglia may promote central disinhibition by selectively phagocytosing inhibitory synaptic terminals [ 84 ] or displacing inhibitory axosomatic presynaptic terminals from cortical neurons [ 85 ]; moreover, blocking microglial activation alleviates PV-IN dysfunction and behavioral changes caused by inflammation or brain injury [ 82 , 83 , 86 ]. In addition, activated microglia may also interfere with the activity of inhibitory synapses by degrading perineuronal nets (PNNs) [ 87 , 88 ], a specialized extracellular matrix structure enwrapping cortical inhibitory fast-spiking PV-INs [ 89 , 90 ]. Our recent work demonstrated that SNI induces the activation of microglia, but not astrocytes, in the bilateral ACC [ 34 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Activated microglia may promote central disinhibition by selectively phagocytosing inhibitory synaptic terminals [ 84 ] or displacing inhibitory axosomatic presynaptic terminals from cortical neurons [ 85 ]; moreover, blocking microglial activation alleviates PV-IN dysfunction and behavioral changes caused by inflammation or brain injury [ 82 , 83 , 86 ]. In addition, activated microglia may also interfere with the activity of inhibitory synapses by degrading perineuronal nets (PNNs) [ 87 , 88 ], a specialized extracellular matrix structure enwrapping cortical inhibitory fast-spiking PV-INs [ 89 , 90 ]. Our recent work demonstrated that SNI induces the activation of microglia, but not astrocytes, in the bilateral ACC [ 34 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Experimental disruption of PNNs mimics the increased capacitance and reduced firing activity of PV neurons as shown by PV neurons with disrupted PNNs in glioma ( Tewari et al, 2018 ), suggesting a pivotal role of PNNs in aiding the fast-spiking properties of PV neurons. PNNs seem to determine the activity of excitatory neurons equally well, as evidenced in a recent study in which microglia-mediated degradation of PNNs around excitatory projection neurons in the spinal cord enhances their activity and induces pain-related behavior ( Tansley et al, 2022 ). Another example is the induction of synaptic plasticity in CA2 neurons upon their PNN depletion, which are otherwise resistant to potentiation ( Carstens et al, 2016 ).…”
Section: Functions Of Perineuronal Netsmentioning
confidence: 91%
“…A similar role of microglia has recently been reported in the spinal cord dorsal horn wherein peripheral nerve injury promotes microglial degradation and endocytosis of PNNs around projection neurons. PNN depletion activates the projection neurons to induce pain-related behavior ( Tansley et al, 2022 ). Despite such explicit presentations of microglial involvement, what triggers microglia to start stripping PNNs and ECM components with or without proteolytic cleavage is still an open question.…”
Section: Extracellular Matrix and Perineuronal Net Remodeling By Micr...mentioning
confidence: 99%
See 1 more Smart Citation
“…Hyper NETosis or ineffective clearance of NETs would likely contribute to the pathogenesis of immune-related diseases ( 8 ). NETs are involved in numerous pathological processes, including infection ( 9 ), autoimmune diseases ( 10 ), tumor development ( 11 ), Alzheimer’s disease ( 12 ), acute ischemic stroke ( 13 ), peripheral nerve injury ( 14 ) and thrombosis ( 8 ). However, its role in neuroimmune diseases remains unclear.…”
Section: Introductionmentioning
confidence: 99%